KNOWLEDGE AND AWARENESS OF ROLE OF DIFFERENT LIGHT SOURCES IN CERAMIC SHADE MATCHING FOR VENEERS AMONG UNDERGRADUATES - Mehrin Bano, Amina; Ganapathy, Dhanraj; Kumar Pandurangan, Kiran (International Journal of Psychosocial Rehabilitation, 2020)
Aesthetic dentistry is a blend of science and art. Its success is determined on the basis of functional and esthetic results. To achieve esthetics, four basic determinants are required in sequence; viz., position, contour, texture, and color. Because esthetic dentistry imposes several demands on the artistic abilities of the dentist and the technician, knowledge of the underlying scientific principles of color is essential. The questionnaire-based study was conducted among the students studying at a private dental college with the aim to assess their knowledge and awareness of the role of different light sources in ceramic shade matching for veneers. A questionnaire was created on Google Forms, and the subjects were administered a structured questionnaire encompassing their knowledge and awareness of the role of different light sources in ceramic shade matching for veneers. The multiple-choice questionnaire developed had 15 questions, and it was made sure that individuals gave their first natural response and attempted all the questions spontaneously. Among the study population, a higher incidence of interns (blue) at 60%, followed by 3rd years (beige) at 23% and 4th years (green) at 17%, was found. Experience was the most commonly chosen answer among interns (blue) at 26% and 3rd years (beige) at 9%; knowledge and experience were chosen equally among 4th years (green) at 6%. The most commonly selected answer was “Yes,” and the highest response was seen among interns (blue) at 55%; among 4th years (green), it was 16%, and among 3rd years (beige), it was 13%. A higher incidence of the correct response (beginning of diagnostic appointment ) among interns (blue) at 26%, 4th years (green) at 10%, and 3rd years (beige) at 15% was seen. A higher incidence of the correct response (85-90 ) among interns (blue) at 23%, followed by 4th years (green) at 6% and 3rd years (beige) at 11%, was seen. To achieve the excellent aesthetic result, the dentist should be able to carry out proper shade selection & communicate it to the lab. From the results of our study we can conclude that the knowledge and awareness of role light source among undergraduates has further room for improvement. Although interns seem to fairly have hold of the concept, more experience and practice in this field is needed for exceptional shade selection skills